Kualitas Semen Cair Kambing Boer dalam Pengencer Air Kelapa Muda dengan Penambahan Sari Kedelai - Sholikah, Nisa'us; Susilowati, Sri; Tribudi, Yuli Arif; Sulistyowati, Deny (Jurnal Veteriner, 2022)
The aim of the study was to determine the quality of the liquid semen of Boer goats stored in young coconut water with the addition of soy milk. The research was conducted at the Animal Reproduction Laboratory, Faculty of Animal Husbandry, Brawijaya University, Malang. The research material was Boer goat semen aged 3 to 4 years collected twice a week using the artificial vaginal method. The research method was laboratory experiment with randomized complete block design with four treatments as a group and each group consist of 10 replications. The data were analyzed by Analyze of Variance. The research treatments were P0 (CEP-3 90% + thin albumen 0.4% + yolk 10%), P1 (coconut water 80% + yolk 15% + soy milk 5%), P2 (coconut water 80% + yolk 10% + soy milk 10%), dan P3 (coconut water 80% + yolk 5% + soy milk 15%). The results showed that the sperm motility and viability until the 3rd day between P0 and P2 treatments did not give a significant difference (P>0.05), but P1 and P3 gave a very significant difference (P<0.01). The percentage of abnormality in all treatments was not significantly different (P>0.05) on day 1 to day 3. P0 could maintain the quality of the liquid semen until the 4th day with individual motility of 43.00 ± 2.88%. Meanwhile, P1 could maintain the quality of liquid semen until the 3rd day with individual motility   of 43.00 ± 1.04%. In conclusion, young coconut water extender with the addition of soy milk could replace Cauda. Epididymal Plasma-3 (CEP-3) extender until the 3rd day for artificial insemination.